Diagnostic Performance of Liquid-Based Versus Conventional Cytology In Body Fluid Examination: A Comparative Study - M, Priyanka; G, Shivashekar (Journal of Neonatal Surgery, 2025)
Cytological examination of serous effusions is a valuable diagnostic tool for detecting malignancies, assessing tumour stage, and identifying inflammatory lesions. However, conventional smear techniques may be limited by low cellularity and obscuring background elements. Liquid-based cytology has emerged as a technique that may overcome these limitations. This study compares the cytomorphological features of body fluids processed by conventional smear and Liquid-based cytology methods. AIM The study compares the cytomorphological features of body fluids processed by conventional cytology and liquid-based cytology. It focuses on evaluating parameters such as cellularity, cell morphology, distribution, background, and architectural preservation for diagnostic accuracy. MATERIALS AND METHODS A cross-sectional analytical study was conducted on 124 body fluid samples, including pleural (n=53), peritoneal (n=53), and bronchial washings (n=18), collected between September 2023 and January 2025. Smears were prepared using both conventional cytology and Liquid-based cytology techniques and stained with Haematoxylin & Eosin, and Papanicolaou stains. Samples were evaluated for cellularity, cell morphology, distribution, background, and architecture using a standardized scoring system. RESULTS Liquid-based cytology smears consistently demonstrated superior performance in terms of cellularity, cell morphology, uniform distribution, and clear background when compared to conventional smears. These differences were statistically significant (p < 0.05) across all sample types, enhancing overall diagnostic yield and interpretability. CONCLUSION Liquid-based cytology offers clear advantages over conventional smears in the evaluation of body fluids, improving the quality and efficiency of cytological assessment. Its adoption in routine practice may aid in more accurate and rapid diagnoses, particularly in effusion cytology